Multifunction coupling catalyst, its preparation method and application
Patent Information
- Application Number
- CN202410180661.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-18
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-18
AI Technical Summary
[0004]目前CO2加氢制备C2+醇反应存在转化率和C2+醇选择性较低等问题,亟需研发一种提高CO2加氢制备C2+醇的转化率和提高C2+醇选择性的催化剂
[0031]相对于现有技术,本发明具有以下有益效果:本发明所提供的多功能耦合催化剂具有优异的CO2转化率和C2+醇选择性,其制备方法简单,操作简便,易于重复和放大生产,具有潜在的工业应用前景。
Smart Images

Figure CN118237032B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a multifunctional coupled catalyst, its preparation method, and its application. Background Technology
[0002] The hydrogenation of CO2 into liquid fuels and chemicals is of great significance for carbon emission reduction and high-value utilization, and plays a positive role in mitigating climate change and reducing dependence on fossil fuels. The products of CO2 hydrogenation include methanol, olefins, aromatics, alkanes, and C6O2. 2+ Alcohols, etc. Among them, C 2+ Alcohols (i.e., straight-chain alcohols with two or more carbon atoms) possess characteristics such as high energy density, high octane number, low vapor pressure, low volatility, good solubility in fuels, and compatibility with existing fuel facilities. They can be used as alternative fuels, oil additives, solvents, chemical raw materials and intermediates (in the production of detergents, pharmaceuticals, and cosmetics), etc., with high added value and wide applications. 2+ Alcohol production methods include grain fermentation and olefin hydration. The former has limited scale and output, and involves a conflict between food and energy resources, while the latter suffers from poor catalyst stability and high dependence on petroleum, contradicting my country's energy structure. CO2 hydrogenation to produce C... 2+ CO2-HAS technology boasts advantages such as short process, high efficiency, and simple operation, making it a highly promising C2H2O technology. 2+ Alternative methods for alcohol production. Catalysts used for CO2-HAS mainly fall into four categories: precious metal, Mo-based, Cu-based, and modified Fischer-Tropsch catalysts. Among them, precious metals are expensive, Mo-based catalysts require harsh reaction conditions, and Cu-based catalysts have excessively high methanol content. Modified Fischer-Tropsch catalysts are inexpensive, readily available, have mild reactions, and produce abundant products, making them the fastest-growing catalyst system. However, the current conversion rates and selectivity of modified Fischer-Tropsch catalysts are still not ideal and cannot meet the requirements of industrial production, necessitating rational catalyst design.
[0003] The key to developing highly efficient catalysts lies in effectively regulating the directed transformation of intermediate species and the precise synthesis of C1-C2 coupling. Reactive coupling is a practical strategy to improve catalytic performance. By combining active components with different functions, it can effectively promote the generation, transfer, and coupling of intermediate species (such as C1 intermediates), thereby improving CO2 conversion and C2-C2 coupling efficiency. 2+Alcohol selectivity and yield. For example, Chinese invention patent application CN113908840A discloses an Fe-based multifunctional catalyst, its preparation method, and its application, which is composed of a Na-ZnFe@C catalyst and a K-CuZnAl catalyst coupled together. Chinese invention patent application CN115722228A discloses a tandem catalyst and a method for preparing low-carbon alcohols with high selectivity; this tandem catalyst is composed of components such as K2O-CuO-ZnO-Fe2O3 and CuO-ZnO-Al2O3-ZrO2. Chinese invention patent application CN115672341A discloses a bifunctional composite metal oxide catalyst, its preparation method, and its application; this bifunctional composite metal oxide catalyst uses zirconium-modified copper-iron oxide as the main catalyst and potassium-modified copper-zinc-aluminum oxide as the co-catalyst. The efficient gradation of the above functional components and reaction conditions is key to control.
[0004] Currently, CO2 hydrogenation is used to produce C 2+ Alcohol reactions involve conversion and C 2+ The low selectivity of alcohols necessitates the development of a method to improve the production of C2 by CO2 hydrogenation. 2+ Alcohol conversion rate and increase C 2+ Alcohol-selective catalysts. Summary of the Invention
[0005] This invention addresses the problems existing in the prior art by providing a multifunctional coupled catalyst, its preparation method, and its application. The catalyst is composed of alkali metal-modified FeIn and K-modified CuZnAl, based on the abundant C1 intermediates (such as CO, CH4) on CuZnAl. x O, COOH, etc.) and abundant CH on Fe-based catalysts x By combining these two components, the reaction network can be regulated, C-C coupling can be strengthened, and efficient, targeted transformation of intermediate species can be achieved, thereby enhancing C-C efficiency. 2+ Alcohol selectivity.
[0006] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:
[0007] The first aspect of the present invention is to provide a multifunctional coupling catalyst, said catalyst being Fe x In-M y Components and CuZnAl-K m The composition is given by the following formula: x is the molar ratio of Fe to In, M is the alkali metal element, and y is the concentration of the alkali metal element in Fe. x In-M y The mass fraction of potassium in CuZnAl-K m The mass fraction in.
[0008] Preferably, the value of x is in the range of 1-5, and more preferably 3.
[0009] Preferably, the value of y ranges from 1 to 5 wt%, more preferably 2 wt%.
[0010] Preferably, the value of m ranges from 1 to 5 wt%, more preferably 3 wt%.
[0011] Preferably, M is selected from one or more of Na, K, Rb, and Cs, and more preferably K.
[0012] Preferably, the Fe x In-M y The component accounts for 20-80% of the total mass of the catalyst, more preferably 50%.
[0013] Preferably, the compounding method includes any one of powder mixing, particle mixing, and layered filling.
[0014] A second aspect of the present invention is to provide a method for preparing the above-mentioned catalyst, the method comprising the following steps:
[0015] 1) Dissolve the Fe salt and In salt to obtain solution L1;
[0016] 2) Dissolve the precipitant containing M to obtain solution L2;
[0017] 3) Mix solutions L1 and L2 and react them. The product is then dried and calcined to obtain Fe. x In-M y ;
[0018] 4) Impregnate CuZnAl with potassium salt, then dry and calcine to obtain CuZnAl-K m ;
[0019] 5) Fe x In-M y and CuZnAl-K m By coupling, a multifunctional coupled catalyst is obtained.
[0020] Preferably, in step 1), the Fe salt and In salt are independently selected from any one of their respective nitrates, chlorides, sulfates, and acetates. More preferably, they are selected from nitrates.
[0021] Preferably, the precipitant containing M in step 2) is selected from one or more of its corresponding carbonate, bicarbonate, and hydroxide. More preferably, it is selected from potassium hydroxide.
[0022] Preferably, the potassium salt in step 4) is selected from one or more of potassium carbonate, potassium bicarbonate, and potassium hydroxide. More preferably, it is selected from potassium carbonate.
[0023] Preferably, the total molar concentration of metal ions in solution L1 in step 1) is 0.5-2 mol / L, more preferably 1 mol / L.
[0024] Preferably, the molar concentration of M in solution L2 in step 2) is 0.5-2 mol / L, more preferably 2 mol / L.
[0025] Preferably, the reaction temperature in step 3) is 20-30℃, the time is 2-12h, and the pH is 8-10.
[0026] Preferably, the drying temperature in steps 3) and 4) is 80-120℃, the drying time is 6-48h, the calcination temperature is 350-450℃, and the calcination time is 2-10h.
[0027] A third aspect of the present invention is to provide a catalyst prepared by the above-described catalyst or the catalyst prepared by the above-described preparation method for the production of C by CO2 hydrogenation. 2+ Applications of alcohols.
[0028] Preferably, the application process is as follows: the loaded multifunctional coupled catalyst is reduced in a specific manner, and then a raw material gas is introduced to react and synthesize C. 2+ alcohol.
[0029] More preferably, the reducing gas is selected from any one of pure H2, pure CO, 10% H2 / Ar, and 10% CO / Ar, the reduction temperature is 300-400℃, and the reduction time is 2-8h.
[0030] More preferably, the feed gas has an H2 / CO2 / N2 ratio of 72 / 24 / 4 and a space velocity of 3000-6000 mLg. cat -1 h -1 The reaction temperature is 240-320℃ and the reaction pressure is 3-5MPa.
[0031] Compared with the prior art, the present invention has the following beneficial effects: the multifunctional coupling catalyst provided by the present invention has excellent CO2 conversion rate and C 2+ The alcohol is selective, and its preparation method is simple, easy to operate, and easy to repeat and scale up, showing potential for industrial application. Attached Figure Description
[0032] Figure 1 Schematic diagram of catalyst loading. Detailed Implementation
[0033] It is worth noting that the raw materials used in this invention are all commercially available products, and their sources are not specifically limited.
[0034] Example 1
[0035] Based on a metal molar ratio of Fe / In = 3, 32.0 g of ferric nitrate nonahydrate and 7.9 g of indium nitrate were weighed and dissolved in deionized water to prepare a 1 mol / L solution L1. 17.8 g of potassium hydroxide was weighed and dissolved in deionized water to prepare a 2 mol / L solution L2. Solutions L1 and L2 were simultaneously added dropwise to a 500 mL beaker. The mixture was stirred at 500 r / min, with a pH of 9, and reacted at 30 °C for 2 h. The mixture was then washed six times with deionized water, centrifuged, and subsequently dried in a 120 °C oven for 12 h. Finally, it was calcined in a muffle furnace at 400 °C for 3 h to obtain Fe3In-K (2 wt%). The K content was determined to be 2.0% using inductively coupled plasma optical emission spectrometry (ICP-OES, Optima 8000, PerkinElmer).
[0036] Weigh 1.1 g of potassium carbonate and dissolve it in 12 mL of deionized water. Weigh 10.0 g of industrial CuZnAl catalyst (purchased from Dalian Ruike Technology Co., Ltd.). Add the prepared potassium carbonate solution dropwise to CuZnAl using the impregnation method, stirring constantly to ensure uniform mixing. After standing for 24 h, place the sample in a 120 °C oven to dry for 12 h, and then calcine it in a muffle furnace at 400 °C for 3 h to obtain CuZnAl-K (3 wt%).
[0037] The Fe3In-K (2wt%) and CuZnAl-K (3wt%) powders were ground at a mass ratio of 1:4 to achieve powder mixing. After tableting and sieving, a 40-60 mesh multifunctional coupled catalyst was obtained. 1.5 g of the catalyst was weighed and mixed with 3.0 g of quartz sand particles (40-60 mesh), and then packed into a fixed-bed isothermal zone (see...). Figure 1 (as shown in a), then CO2 hydrogenation is performed to prepare C. 2+ Performance evaluation of the alcohol. Before the reaction, reduction is required at 350℃ for 3 hours in an H2 atmosphere. After reduction, the temperature is lowered to 280℃, and a feed gas with an H2 / CO2 / N2 ratio of 72 / 24 / 4 is introduced at a space velocity of 3000 mL / g. cat -1 h -1 The reaction temperature was 320℃ and the reaction pressure was 3MPa. The performance results are shown in Table 1.
[0038] Example 2
[0039] The sample preparation method, filling method and evaluation process are the same as in Example 1, except that the mass ratio of Fe3In-K (2wt%) and CuZnAl-K (3wt%) is 2:3. The performance results are shown in Table 1.
[0040] Example 3
[0041] The sample preparation method, filling method and evaluation process are the same as in Example 1, except that the mass ratio of Fe3In-K (2wt%) and CuZnAl-K (3wt%) is 1:1. The performance results are shown in Table 1.
[0042] Example 4
[0043] The sample preparation method, filling method and evaluation process are the same as in Example 1, except that the mass ratio of Fe3In-K (2wt%) and CuZnAl-K (3wt%) is 3:2. The performance results are shown in Table 1.
[0044] Example 5
[0045] The sample preparation method, filling method and evaluation process are the same as in Example 1, except that the mass ratio of Fe3In-K (2wt%) and CuZnAl-K (3wt%) is 4:1. The performance results are shown in Table 1.
[0046] Comparative Example 1
[0047] Based on a metal molar ratio of Fe / In = 3, 32.0 g of ferric nitrate nonahydrate and 7.9 g of indium nitrate were weighed and dissolved in deionized water to prepare a 1 mol / L solution L1. 17.8 g of potassium hydroxide was weighed and dissolved in deionized water to prepare a 2 mol / L solution L2. Solutions L1 and L2 were simultaneously added dropwise to a 500 mL beaker. The mixture was stirred at 500 r / min, with a pH of 9, and reacted at 30 °C for 2 h. The mixture was then washed six times with deionized water, centrifuged, and subsequently dried in a 120 °C oven for 12 h. Finally, it was calcined in a muffle furnace at 400 °C for 3 h to obtain Fe3In-K (2 wt%). The K content was determined to be 2.0% using inductively coupled plasma optical emission spectrometry (ICP-OES, Optima 8000, PerkinElmer).
[0048] The Fe3In-K (2wt%) and CuZnAl were ground at a mass ratio of 1:1 to achieve powder mixing. After tableting and sieving, a 40-60 mesh multifunctional coupled catalyst was obtained. 1.5 g of the catalyst was weighed and mixed with 3.0 g of quartz sand particles (40-60 mesh), and then packed into a fixed-bed isothermal zone. CO2 hydrogenation was then performed to produce C. 2+ Performance evaluation of the alcohol. Before the reaction, reduction is required at 350℃ for 3 hours in an H2 atmosphere. After reduction, the temperature is lowered to 280℃, and a feed gas with an H2 / CO2 / N2 ratio of 72 / 24 / 4 is introduced at a space velocity of 3000 mL / g. cat -1 h -1 The reaction temperature was 320℃ and the reaction pressure was 3MPa. The performance results are shown in Table 1.
[0049] Comparative Example 2
[0050] The sample of Comparative Example 2 was a composite of CuZnAl-K (3wt%) from Example 1 and Fe3In without alkali metal modification. The preparation process of Fe3In was the same as in Example 1, except that the precipitant was replaced by 15.2g of anhydrous ammonium carbonate instead of potassium hydroxide. The mass ratio, loading method, and evaluation process of this composite catalyst were the same as in Example 3, and its performance results are shown in Table 1.
[0051] Table 1. Catalytic performance results of Examples 1-5 and Comparative Examples 1-2
[0052]
[0053]
[0054] Table 1 shows that the catalytic performance of Fe3In-K (2wt%) and CuZnAl-K (3wt%) powders mixed at different mass ratios varies significantly. The highest Cc can be obtained when the mass ratio is 1:1. 2+ The alcohol selectivity was 40.3%. Furthermore, the catalytic performance of the mixture of Fe3In-K (2wt%) and CuZnAl-K (3wt%) was significantly better than that of the mixture of Fe3In-K (2wt%) and CuZnAl or the mixture of Fe3In and CuZnAl-K (3wt%).
[0055] Example 6
[0056] The sample preparation method and evaluation process were the same as in Example 1, except for the loading method of the multifunctional coupled catalyst. Specifically: Fe3In-K (2wt%) and CuZnAl-K (3wt%) were first compressed into tablets and sieved to obtain 40-60 mesh particles. Then, 0.75 g of Fe3In-K (2wt%) particles and 0.75 g of CuZnAl-K (3wt%) particles were weighed at a mass ratio of 1:1 and mixed with 3.0 g of quartz sand particles (40-60 mesh). This mixture was then loaded into a fixed-bed isothermal zone (see [link to relevant documentation]). Figure 1 (as shown in b in the figure). Its performance results are shown in Table 2.
[0057] Example 7
[0058] The sample preparation method and evaluation process were the same as in Example 1, except for the loading method of the multifunctional coupled catalyst. Specifically: Fe3In-K (2wt%) and CuZnAl-K (3wt%) were first compressed into tablets and sieved to obtain 40-60 mesh particles. 0.75g of Fe3In-K (2wt%) was mixed with 1.5g of quartz sand particles (40-60 mesh) and loaded into the upper layer of the fixed-bed isothermal zone. 0.75g of CuZnAl-K (3wt%) was mixed with 1.5g of quartz sand particles (40-60 mesh) and loaded into the lower layer of the fixed-bed isothermal zone. The two layers were separated by quartz wool (see [link to example]). Figure 1 (As shown in c in the figure). Its performance results are shown in Table 2.
[0059] Example 8
[0060] The sample preparation method and evaluation process were the same as in Example 1, except for the loading method of the multifunctional coupled catalyst. Specifically, 0.75 g of Fe3In-K (2 wt%) was mixed with 1.5 g of quartz sand particles (40-60 mesh) and loaded into the lower layer of the fixed-bed isothermal zone; 0.75 g of CuZnAl-K (3 wt%) was mixed with 1.5 g of quartz sand particles (40-60 mesh) and loaded into the upper layer of the fixed-bed isothermal zone. The two layers were separated by quartz wool (see [link to documentation]). Figure 1 (As shown in d in the figure). Its performance results are shown in Table 2.
[0061] Table 2 Catalytic performance results of Examples 3 and 6-8
[0062]
[0063] Table 2 shows that, under the same mass ratio, the loading method of Fe3In-K (2wt%) and CuZnAl-K (3wt%) affects the catalytic performance. 2+ In terms of alcohol selectivity, powder mixing is superior to particle mixing and layered filling.
[0064] Example 9
[0065] The sample preparation method, loading method, and evaluation process were the same as in Example 3, except that the K-modified FeIn oxide was changed to Fe1In-K (2wt%), that is, based on the metal molar ratio Fe / In = 1, the masses of ferric nitrate nonahydrate and indium nitrate became 21.4 g and 15.8 g, respectively. The performance results are shown in Table 3.
[0066] Example 10
[0067] The sample preparation method, filling method, and evaluation process were the same as in Example 3, except that the K-modified FeIn oxide was changed to Fe5In-K (2wt%), that is, based on the metal molar ratio Fe / In = 5, the masses of ferric nitrate nonahydrate and indium nitrate became 35.6 g and 5.2 g, respectively. The performance results are shown in Table 3.
[0068] Table 3. Catalytic performance results of Examples 3 and 9-10
[0069]
[0070] Table 3 shows that the Fe / In molar ratio affects catalytic performance; a higher Fe / In ratio increases CO2 conversion, but when Fe / In = 3, C... 2+ Alcohols exhibit the highest selectivity.
[0071] Example 11
[0072] The sample preparation method, filling method, and evaluation process were the same as in Example 3, except that the precipitant was changed from potassium hydroxide to sodium hydroxide, with a mass of 12.7 g. The performance results are shown in Table 4.
[0073] Example 12
[0074] The sample preparation method, filling method, and evaluation process were the same as in Example 3, except that the precipitant was changed from potassium hydroxide to rubidium carbonate, with a mass of 36.6 g. The performance results are shown in Table 4.
[0075] Example 13
[0076] The sample preparation method, filling method, and evaluation process were the same as in Example 3, except that the precipitant was changed from potassium hydroxide to cesium carbonate, with a mass of 51.6 g. The performance results are shown in Table 4.
[0077] Table 4. Catalytic performance results of Examples 3 and 11-13
[0078]
[0079] From the data in Table 4 and Example 3, it can be seen that the type of alkali metal affects the catalytic performance. When K is introduced into the FeIn system, C 2+ Alcohols exhibit the highest selectivity.
[0080] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.
Claims
1. A multifunctional coupling catalyst, characterized in that, The catalyst is composed of Fe x In-M y Components and CuZnAl-K m The composition is given by the following formula: x is the molar ratio of Fe to In, M is the alkali metal element, and y is the percentage of the alkali metal element in Fe. x In-M y The mass fraction, m, represents the proportion of potassium in CuZnAl-K m The mass fraction; wherein, the value of x is 3, the value of y ranges from 1 to 5 wt%, and the value of m ranges from 1 to 5 wt%; the Fe x In-M y The component accounts for 50-80% of the total mass of the catalyst.
2. The catalyst according to claim 1, characterized in that, M is selected from one or more of Na, K, Rb, and Cs.
3. The catalyst according to claim 1, characterized in that, The coupling method of the catalyst is selected from any one of powder mixing, particle mixing, and layered loading.
4. A method for preparing the catalyst according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: 1) Dissolve the Fe salt and In salt to obtain solution L1; 2) Dissolve the precipitant containing M to obtain solution L2; 3) Mix solutions L1 and L2 and react them. The product is then dried and calcined to obtain Fe. x In-M y ; 4) Impregnate CuZnAl with potassium salt, then dry and calcine to obtain CuZnAl-K m ; 5) Fe x In-M y and CuZnAl-K m By coupling, a multifunctional coupled catalyst is obtained.
5. The preparation method according to claim 4, characterized in that, In step 1), the Fe salt and In salt are independently selected from any one of their respective nitrates, chlorides, sulfates and acetates; in step 2), the precipitant containing M is selected from one or more of its respective carbonates, bicarbonates and hydroxides; in step 4), the potassium salt is selected from one or more of potassium carbonate, potassium bicarbonate and potassium hydroxide.
6. The preparation method according to claim 4, characterized in that, In step 1), the total molar concentration of metal ions in solution L1 is 0.5-2 mol / L; in step 2), the molar concentration of M in solution L2 is 0.5-2 mol / L; in step 3), the reaction temperature is 20-30℃, the time is 2-12 h, and the pH is 8-10.
7. The preparation method according to claim 4, characterized in that, The drying temperature in steps 3) and 4) is 80-120℃, the drying time is 6-48h, the calcination temperature is 350-450℃, and the calcination time is 2-10h.
8. A catalyst according to any one of claims 1-3 or a catalyst prepared by any one of claims 4-7 for the production of C by CO2 hydrogenation. 2+ Its application in alcohols is characterized by, The application process is as follows: the loaded multifunctional coupled catalyst is reduced in a specific manner, and then feed gas is introduced to carry out the reaction to synthesize C. 2+ The reducing gas used in the reduction is selected from any one of pure H2, pure CO, 10% H2 / Ar, and 10% CO / Ar; the reduction temperature is 300-400℃; and the reduction time is 2-8h. The feed gas has an H2 / CO2 / N2 ratio of 72 / 24 / 4 and a space velocity of 3000-6000 mLg. cat -1 h -1 The reaction temperature is 240-320℃ and the reaction pressure is 3-5MPa.
Citation Information
Patent Citations
Fe-based multifunctional catalyst as well as preparation method and application thereof
CN113908840A
Tandem catalyst and high-selectivity preparation method of low-carbon alcohol
CN115722228A
Difunctional composite metal oxide catalyst as well as preparation method and application thereof
CN115672341A
Preparation method and application of indium-based catalyst for synthesizing low-carbon alcohol through hydrogenation of carbon dioxide
CN116099540A